Knowledge management in the public sector – the case of Serbian local government - Mitrović, Zorica; Obradović, Vladimir; Suknović, Milija (Serbian Journal of Management, 2018)
Knowledge has become an increasingly important determinant of competitiveness for the local governments. The purpose of this paper was to explore the existence of KM in Serbian local government and to identify and analyzes processes and infrastructure that supports KM practices. The paper consists of two parts; the first part covers comprehensive literature review that summarizes the existing research done on the subject of knowledge management in public sector in order to put research in context and to highlight the contribution of this paper to the existing body of knowledge. The second part consists of empirical research conducted to get a preview of the current state of the KM practice in Serbian local government. There were several important findings regarding KM practices in Serbian LGs identified in the study, i.e., public servants have a positive attitude toward KM concept; KM activities are mostly technology supported; KM is perceived as a management priority; there is not any formal attribution of responsibility for knowledge practice to executive staff, human resource unit or IT unit, neither any mention of knowledge capacity development in strategies or plans of LGs. Finally, the results of this research study provide valuable guidance for future research for both academics and practitioners.